التلفزيون وتأثراته المحتملة على جمهور الأطفال - نغيمش الحمامي, الدكتور: هاشم أحمد، (Sciences de l'Homme et de la Société; Vol. 14 (2015): SCIENCES DE L'HOMME ET DE LA SOCIÉTÉ(Mars), 2015)
يعالج هذا البحث قضية التاثيرات المحتملة للتلفزيون على جمهور الاطفال، ويتطرق الى التاثيرات السلبية والايجابية التي يحتمل تاثر جمهور الاطفال المتابعين للتلفزيون بها، كما انه يتطرق الى مسالة ثقافة الاطفال وطرق اكتسابهم للمعرفة وكيفية تاثرهم بما يشاهدونه في التلفزيون، وفضلا عن ذلك فان هذا البحث يحاول التوصل الى شكل ومحتوى البرامج التلفزيونية التي تناسب جمهور الاطفال، والتي يمكن ان تساهم في احداث التاثيرات الايجابية في جمهور الاطفال. Abstract : This study examines the issue of the potential effects of television on children, And talked about the negative impacts and positive effects, which are likely affected by the kids observers of the TV. It also addresses the issue of children's culture, and the ways in which they acquire knowledge and how children are affected by what they see on TV, This study also trying to reach the form and content of television programs that fit audience of children. This study found significant results, including: that television has positive and negative effects on children, on the positive effects enhance self-confidence and respect for others, children learn some social skills, develop some mental capacity, enhance the sense of social responsibility in children, as well as recreation for children and reduce conflicts within the family.